Amalgamation of g-C3N4 with KNbO3 for enhanced removal of Bisphenol A under sunlight irradiation. Issue 1 (December 2021) - Song, Bing Cong; Sim, Lan Ching; Chin, Yik Heng; Wong, Ling Yong; Saravanan, Pichiah; Dai, Chaomeng; Leong, Kah Hon
Abstract: Bisphenol A (BPA) is a pollutant exits in an enormous amount in wastewater effluent resulted from the rapid industrialization. Advanced oxidation technology (AOP) based on solar photocatalysis can be employed to solve this issue. This study will focus on adopting photocatalyst graphitic carbon nitride (g-C3 N4 ) with potassium niobate (KNbO3) via a simple sol-gel synthesis method. The different weight percentages 0.5, 1.0 and 1.5 wt% g-C3 N4, were adopted to formed KNbO3 /g-C3 N4 composites. The physicochemical properties of the created KNbO3 /g-C3 N4 composites were characterized with advanced analysis methods to unveil this composite's ability to enhance the photodegradation of BPA under sunlight irradiation. It was found that 1.0 wt% KNbO3 /g-C3 N4 composites exhibited the highest photocatalytic degradation of 69.39% in 5 h. This superior photodegradation of BPA was achieved resulted from the presence of g-C3 N4 that enhances light-harvesting, especially in the visible light spectrum. The increase of light-harvesting enables the composite to excite more electrons and holes leading to the massive formation of active radicals. These massive active radicals will then enhance the redox reaction and further improve the efficacy of the photodegradation of BPA. Hence, the outcome of this study path an alternative solution for eliminating complex organic pollutants in wastewater treatment.